Buy baits and consumer sophistication: Theory and field evidence from large-scale rebate promotions - Matthias Rodemeier (Westfälische Wilhelms-Universität Münster, Centrum für Angewandte Wirtschaftsforschung (CAWM), 2021)
Can firms exploit behavioral biases to increase profits? Does consumer sophistication about these biases limit the scope of exploitation? To answer these questions, I run a series of natural field experiments with over 600,000 consumers and estimate novel sufficient statistics of consumer sophistication. The empirical application is a ubiquitous and widely regulated form of price discrimination: rebates that need to be actively claimed by consumers. These promotions are suspected of boosting sales even though many consumers eventually fail to claim the rebate-a phenomenon marketers refer to as "slippage." I show theoretically that consumers' subjective redemption probabilities can be inferred from how demand responds to rebates as opposed to simple price reductions. I identify these elasticities in three natural field experiments with a major online retailer, in which I randomize prices, redemption requirements, and reminders. Results reveal that claimable rebates in fact increase sales substantially even though 47% of consumers do not redeem the rebate. However, consumers exhibit a remarkable degree of sophistication: the demand response to a rebate is only 76% of the demand response to an equivalent price reduction. Structural estimates imply that consumers almost perfectly anticipate their inattention but vastly underestimate the hassle of redemption by 20 EUR per consumer. Exploiting this misperception increases the profitability of rebates by up to 260%.
Keywords: D18; D61; D83; D49; D90; 330; consumer sophistication; price discrimination; field experiments; behavioral public economics